2020
DOI: 10.1136/annrheumdis-2020-218147
|View full text |Cite
|
Sign up to set email alerts
|

Response to: ‘Correspondence on Recovery from COVID-19 in a patient with spondyloarthritis treated with TNF-alpha inhibitor etanercept. A report on a COVID-19 patient with psoriatic arthritis receiving ustekinumab’ by Messina et al

Abstract: Patient and public involvement Patients and/or the public were not involved in the design, or conduct, or reporting, or dissemination plans of this research. Patient consent for publication Not required.Provenance and peer review Commissioned; internally peer reviewed. This article is made freely available for use in accordance with BMJ's website terms and conditions for the duration of the covid-19 pandemic or until otherwise determined by BMJ. You may use, download and print the article for any lawful, non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Our results are similar to those reported by Duret et al [8] and the use of DMARDs does not seem to contribute to an unfavorable evolution of COVID-19. Rheumatologists however should pay special attention to the use of rituximab as, due to its distinct mechanism of action, may be associated to complications and a worse outcome in SARS-CoV-2 infection.…”
supporting
confidence: 92%
“…Our results are similar to those reported by Duret et al [8] and the use of DMARDs does not seem to contribute to an unfavorable evolution of COVID-19. Rheumatologists however should pay special attention to the use of rituximab as, due to its distinct mechanism of action, may be associated to complications and a worse outcome in SARS-CoV-2 infection.…”
supporting
confidence: 92%
“…Our systematic search of the literature allowed us to identify 37 case reports and case series 20‐56 and 11 studies that corresponded to our research question but their data were provided descriptively and an effect measure could not be calculated 21,57‐66 . These data are included in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Some case reports emphasized that patients on TNF-α blockers due to rheumatological diseases were infected by Covid-19 during their treatment; nevertheless, there was no deterioration in disease prognosis. In fact, it was suggested that the use of other anti-inflammatory drugs for Covid-19 was beneficial in disease prognosis (17).Accordingly, TNF-α blockers may be considered in Covid-19 patients with DM, who develop excessive inflammation. Efficacy of steroids as a treatment option for Covid-19 infections has been suggested in cases of hypoxemia (18).…”
Section: Discussionmentioning
confidence: 99%